1998
DOI: 10.3109/01913129809032281
|View full text |Cite
|
Sign up to set email alerts
|

A New Immunoelectron Microscopy Approach for the Detection of Immunoglobulin and Complement Deposits in E poxy-Embedded Renal Biopsies

Abstract: The purpose of this study was to examine the diagnostic value of a new immunoelectron microscopy technique (IEM) for detection of immunoglobulin and complement deposits in epoxy-embedded renal biopsies. Twenty-four renal biopsies were embedded in epoxy resin following a tissue processing involving moderately increased amount of accelerator, DMP-30 (Tri(Dimethyl Amino Methyl) Phenol), in the infiltration steps. Following antigen retrieval by heating in citrate buffer, immunogold labeling was performed on ultrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Unlike some other studies, we did not require further antigen retrieval to successfully immunolabel our epoxy sections. Previous studies have found that antigen retrieval by heating in citrate buffer (Stirling and Graff 1995;Brorson and Strøm 1998;Groos et al 2001), Tris-HCl (Yamashita et al 2009), or alkaline solutions (Yano et al 2003) significantly increased immunlabeling probe density over that obtained with etching alone. Other aspects, such as an increased amount of accelerator in epoxy resin (Brorson 1998a), the use of propylene oxide in specimen processing (Brorson 1996), the sectioning process itself (Hann et al 2001), and osmication of tissue (Brorson 2004), have also been shown to affect antigen retrieval from epoxy sections.…”
Section: Discussionmentioning
confidence: 97%
“…Unlike some other studies, we did not require further antigen retrieval to successfully immunolabel our epoxy sections. Previous studies have found that antigen retrieval by heating in citrate buffer (Stirling and Graff 1995;Brorson and Strøm 1998;Groos et al 2001), Tris-HCl (Yamashita et al 2009), or alkaline solutions (Yano et al 2003) significantly increased immunlabeling probe density over that obtained with etching alone. Other aspects, such as an increased amount of accelerator in epoxy resin (Brorson 1998a), the use of propylene oxide in specimen processing (Brorson 1996), the sectioning process itself (Hann et al 2001), and osmication of tissue (Brorson 2004), have also been shown to affect antigen retrieval from epoxy sections.…”
Section: Discussionmentioning
confidence: 97%